Mind-as-Body as a Cross-Linguistic Conceptual Metaphor - Iraide Ibarretxe-Antuñano (Miscelánea: A Journal of English and American Studies, 2002)
The conceptual metaphor MIND-AS-BODY (Sweetser 1990) is motivated by correspondences between our external experience (i.e. body) and our internal emotional and cognitive states (i.e. mind). Taking Sweetser's work on English perception verbs as the starting point, I will analyse in this paper the different semantic extensions that take place in this semantic field. I will focus on two main points: first, I will show how the metaphorical scope of these verbs is even larger than that proposed by Sweetser and second, I will provide further support for her claim that these mappings are cross-linguistic. The languages under investigation are two Indo-European languages, English (Germanic) ans Spanish (Romance), and one non-Indo-European, Basque.
Keywords: cognitive semantics; cross-linguistic metaphor; perception verbs